Evaluation of Ecotourism Practices: A Comparative Study of Lowlands and Mountains of Nepal - Khanal, Bibek; Gosai, Kamal Raj (Journal of Tourism and Himalayan Adventures, 2024)
This research provides valuable insights into tourist profiles, market demand, attractions, motivations, amenities, and satisfaction levels in Chitwan National Park (CNP), the lowland park, and Annapurna Conservation Area (ACA), the park in the mountains of Nepal. Through qualitative and quantitative research methods, including surveys, interviews, and field observations, this study compared the current state of ecotourism practices in the protected areas (PAs). Though both the PAs showed consistent growth in tourist flow, ACA exhibited signs of saturation, suggesting the need for strategic management. Attractions differed in the PAs; natural scenery and photography draw visitors to ACA while wildlife and cultural experiences attract tourists to CNP. Disparities in amenities highlight areas for improvement, particularly in ACA. Community engagement is always an added benefit to any tourism development. Overall, satisfaction levels are satisfactory, but challenges such as overcrowding, decreasing quality of tourism, environmental degradation, and accessibility constraints require attention for sustainable tourism development. Collaborative efforts can address these issues and ensure the long-term viability of ecotourism in CNP and ACA while preserving their natural and cultural heritage.